Microstructural characterization of high-performance steel fiber reinforced geopolymer concrete - Zoi G. Ralli; Stavroula J. Pantazopoulou; Vladimiros G. Papangelakis (Acta Polytechnica CTU Proceedings, 2022)
Due to growing environmental and economic concerns associated with conventional building materials, research interest gravitates towards the development of novel environmentally friendly materials as alternatives to conventional Portland cement concrete. Geopolymer concrete is a class of novel advanced and sustainable structural materials that hold promise for the future of infrastructure. Its synthesis comprises industrial by-products (fly ash and slag among others) in the role of binder and thus reduces the demand in Portland cement leading to a significant carbon footprint reduction. In the present study a High-Performance Fiber Reinforced Geopolymer Concrete (HPFRGC) is synthesized from first principles and is subsequently characterized, with particular emphasis on its microstructural and mineralogical properties. The study explores the linkage between the microstructure and mineralogy of the precursors, and the properties of the final product. Both fresh and hardened HPFRGC are studied. Experimental results illustrate the correlation between microstructure, mineralogy and final mechanical properties can be used as an indicator of suitability of industrial by-products for geopolymer precursors. The effect of these choices on stability and physical properties of the material is also explored in the study.